Pandangan Dunia Pengarang dalam Novel Ayah Keduaku Karya Mohd Amin Ms Telaah Strukturalisme Genetik Goldmann - Murnilawati Murnilawati; Fadlillah Fadlillah; Zurmailis Zurmailis (Universitas Andalas, 2023)
This thesis discusses the world view in the novel Ayah Keduaku by Mohd Amin Ms. The purpose of this research is to find out the author's worldview that appears in the novel Ayah keduaku, where there are several worldviews of Mohd Amin, namely, first, Mohd Amin's worldview on the difference between General Education and Islamic Education. The second view is the difference in attitudes towards immigrants and indigenous people who serve as regents in Kampar. The third view, namely the view of the political conflict against the Malay family that occurred in the confrontation between Indonesia and Malayasia.This study uses the dialectical method developed by Lucien Goldmann. The basic principle of the dialectical method is the principle that it works through knowledge of human facts connected by integrating them into the whole. The work step in this research is to read and understand the object and collect data related to the object in the research, and then analyzed using the theory of genetic structuralism. To formulate the author's world view, social structure is discussed, namely the background of the author's social life is the Pujud area. In this case Mohd Amin Ms and the history of the formation of an author's work come from Pujud. So his work is related to the author's place of origin in Pujud. The author's view of his work is the view of the author who represents his community group which illustrates some of the views raised in the novel Ayah Keduaku. Genetics structuralism is a literary work that discusses space and time. Meanwhile, the social structure consists of the background of the author's social life and the history of the publication of the novel My Second Father as well as the author's worldview regarding his work. From the results of the research, it is suggested that students of Indonesian language and literature can use Lucian Goldmann's study of genetic structuralism with novels with social nuances and for readers to gain an understanding of the author's worldview based on the theory of genetic structuralism so that they can develop further research in the same field.